Cloud computing with e-science applications - Terzo, Olivier; Mossucca, Lorenzo (CRC Press, 2015)
This book describes how cloud computing can significantly improve data management in different scientific fields, such as bioinformatics, earth science, and computer science. This book focuses on how cloud computing helps in the areas of resource control, vertical and horizontal scalability, and adaptive scheduling.